Carbon Nanomaterial-Based Nanofluids for Direct Thermal Solar Absorption - Nguyen Trong Tam; Nguyen Viet Phuong; Phan Hong Khoi; Phan Ngoc Minh; Masoud Afrand; Pham Van Trinh; Bui Hung Thang; Gaweł Żyła; Patrice Estellé (Nanomaterials, 2020)
Recently, many scientists have been making remarkable efforts to enhance the efficiency of direct solar thermal absorption collectors that depends on working fluids. There are a number of heat transfer fluids being investigated and developed. Among these fluids, carbon nanomaterial-based nanofluids have become the candidates with the most potential by the heat absorbing and transfer properties of the carbon nanomaterials. This paper provides an overview of the current achievements in preparing and exploiting carbon nanomaterial-based nanofluids to direct thermal solar absorption. In addition, a brief discussion of challenges and recommendations for future work is presented.